From Access to Communion Beyond the Social Model - Hinojosa, Victor J. (2018)
The author discusses the public policy implications of current models of disability, arguing that the Americans with Disabilities Act represents the shift from medical to social models and that this shift has resulted in significant progress toward social and economic inclusion for those with disabilities. Yet this vision of society remains incomplete, as the current emphasis on individual accommodation has not led to fundamental social transformation. Drawing on resources in contemporary theologies of disability, the witness of L'Arche, and the author's experience as the parent of a child with significant intellectual and physical disabilities and complex medical needs, the essay calls those with and without disabilities to a life of communion and mutual giving and receiving.
Keywords: L'Arche; Disability Studies; Intellectual disability; parent